PERILAKU HUMOR PEMIMPIN DAN WORK-FAMILY BALANCE KARYAWAN: SEBUAH PENJELASAN DARI MEKANISME LEADER- MEMBER EXCHANGE DI BPJS KETENAGAKERJAAN WILAYAH SUMBARRIAU - Afit, Ray Boni; Abdillah, M. Rasyid; Zamzami, Zamzami (Jurnal Daya Saing, 2025)
This study aims to analyze the effect of leader humor behavior on employees’ work-family balance (WFB) with Leader-Member Exchange (LMX) as a mediating variable. The balance between work and family life has become an important issue in modern human resource management, particularly in public institutions such as BPJS Ketenagakerjaan, which demands both high performance and psychological well-being. This research applies a quantitative approach using a survey method involving 160 respondents from BPJS Ketenagakerjaan Regional Office of Sumbarriau. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 5.0 software. The results reveal that leader humor behavior positively and significantly influences LMX and WFB, and LMX significantly mediates the relationship between leader humor and work-family balance. These findings emphasize that positive humor strengthens the emotional connection between leaders and subordinates, thereby enhancing employees’ psychological well-being. Theoretically, this study expands the understanding of social exchange theory within the context of humanistic leadership, while practically offering implications for developing leadership styles that promote work-life harmony.